(untitled) (Global Journal of Sciences, 2026)
The majority of the material called lignocellulose biomass (LCB), a type of plant biomass, is made up of these three compounds. The most common polymer to break down on Earth is cellulose, which is very useful and has many uses. Because cellulose is securely linked to the compound’s hemicellulose and lignin in lignocellulosic materials, it is highly challenging to separate the material from LCB components; therefore, effective pretreatment techniques are required to make the material separation easier. Green pretreatment approaches have been proposed as a gentler and more environmentally responsible way to address these problems. When assessing these green processes, a variety of factors are taken into account, such as the effectiveness of delignification with a lower solvent demand, the impact on the environment, the economic feasibility, and the suitability for new sustainable processing solutions. We also assessed how using biomass affected land use, production of greenhouse gases, and group effects, among other socioeconomic and environmental factors. This paper examines the challenges, ongoing research, and recent developments in effective biomass-based energy systems to increase energy output while lowering environmental concerns. Additionally, it provides a summary of how cellulose is separated from various lignocellulosic biomass using sustainable and green methods.